Lexical and Semantic Parallels of Yakut and Telengit Folklore Prose - Marina T. Gogoleva; Lyudmila S. Tutukarova (Publishing house "Sreda", 2021)
Interest in the research topic arose as a result of studying the texts of folklore prose of the Yakuts and Telengits. Used method, i.e. reliance on scientific works, collection of facts, comparative analysis of lexical-semantic parallels led to interesting results. The identified samples from the folklore of peoples separated by a huge distance and an independent history of development indicate the presence of common roots. Legends reflect the peculiarities of the ideological ideas of ethnic groups, spiritual and moral values, religious views; at the same time, commonality is found not only in the lexico-semantic plan, but also in the compositional structure of the presentation of the material and the syntax of texts. The changes are quite insignificant, for example, in the Yakut version of the legend «Dispute» the image of a large animal is transformed in accordance with the realities of the Arctic nature, for example, a camel turns into an elk. The thematic approach to the consideration of examples allows us to come to the conclusion that most of the coincidences fall on the texts of religious and everyday content. Some examples from onomastics also speak of ancient linguistic contacts or testify to migration processes among the Turkic-speaking ethnic groups, which have not yet received proper coverage in historical science. In the conclusion of the article, it is said about the need to attract more extensive material to the comparative historical study of the phenomenon. Based on the comprehension of the collected material, an assumption is made about the stability of individual lexemes and lexical-semantic constructions in the translation of the traditional beliefs of the people.